Sharing Knowledge For Creative Product Development In A Malaysian Electronics Company - Ng, Poh Kiat; Jee, Kian Siong (Journal of Knowledge Management Practice, 2012)
The purpose of this paper is to investigate the influence of knowledge management on creative product development in a Malaysian electronics company. Using a survey-based method, a total of 226 survey responses were collected back from product development personnel. These were then analyzed using reliability, linear regression and multiple linear regression analysis. It was found that combination had the strongest influence on creative product development. Despite the drawback in socialization’s influence, it would be still be beneficial for this company to provide more room for socialization activities to enrich the idea generation for more creative product development performance. This study stresses on the applied mechanism of knowledge sharing in an electronics company with an emphasis on creative product development, which is important for other electronics companies to identify for a sustainable competitive advantage in the market. The findings suggest key implications for the practice and research concerning knowledge management and product development in companies and related initiatives.